2020
DOI: 10.24191/ajue.v16i3.10311
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Scientific Reasoning Skills Of Science Education Students

Abstract: The article discusses a study carried out to investigate scientific reasoning skills among 82 science pre-service teachers at the Faculty of Education, Universiti Teknologi MARA (UiTM), one of the public universities in Malaysia. The development of general scientific abilities is critical to enable students of science, technology, engineering, and mathematics (STEM) to successfully handle open-ended real-world tasks in their future careers. Teaching goals in STEM education include fostering content knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Kondisi tersebut mengharuskan seorang guru juga harus memiliki penalaran ilmiah yang baik. Guru fisika harus memiliki penalaran ilmiah yang baik karena hal inilah yang secara potensial dapat membimbing siswa untuk memiliki penalaran ilmiah yang baik pula (Zulkipli et al, 2020).…”
Section: Pendahuluanunclassified
“…Kondisi tersebut mengharuskan seorang guru juga harus memiliki penalaran ilmiah yang baik. Guru fisika harus memiliki penalaran ilmiah yang baik karena hal inilah yang secara potensial dapat membimbing siswa untuk memiliki penalaran ilmiah yang baik pula (Zulkipli et al, 2020).…”
Section: Pendahuluanunclassified
“…Drawn from the premise that the main processes developed in a science classroom are based on language and social relationships, it can affirmed that students' interest can make them easier to speak about science (Kelly, 2007), mainly if teachers foster it with inquiry based activities and contextualization (STS), (Jiménez-Aleixandre, 2010). In the last few years, it has been observed that the science class activities that develop the reasoning competence are clearly recommendable for achieving the pursued literacy on scientific competence (Erduran & Jiménez-Aleixandre, 2007;Bricker & Bell, 2008, Zulkipli et al, 2020.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Introduction of curriculum, pedagogy and assessment that emphasize this HOTS added to the basic Primary School Standard Curriculum (KSSR) which was first introduced in 2011. The creation of this curriculum to replace the Integrated Primary School Curriculum (KBSR) requires learning to apply the concept of Islamic education and practice in everyday life in line with the emphasis which is pressed in the Quran and Sunnah (Zulkipli et al, 2020).…”
Section: Abilities Generate Ideasmentioning
confidence: 99%